Connotation, pathways, and significance of building China into an “energy powerhouse”; - Caineng ZOU; Shixiang LI; Bo XIONG; Zhi YANG; Hanlin LIU; Guosheng ZHANG; Feng MA; Songqi PAN; Chunxiao GUAN; Yingbo LIANG; Boning TANG; Songtao WU; et al. (Petroleum Exploration and Development)
By summarizing the characteristics of the global energy structure and China's energy resource endowment, this study analyzes the historical context and opportunities for China to build an “energy powerhouse”;, and proposes pathways and measures for its realization. It is indicated that the energy resource endowment in China is characterized by abundant coal, limited oil and gas, and vast renewable potential, coupled with an energy consumption structure characterized by high coal consumption, low oil and gas consumption, and rapidly growing renewable energy use. The “whole-energy system”; approach that integrates multi-energy complementarity, green development, stable supply, smart utilization and carbon neutrality is an effective solution to addressing energy transition and energy independence. To build an “energy powerhouse”;, China can follow the approach of the steady and orderly low-carbon development of fossil fuels, the safe and scaled development of new energy, the integrated development of a carbon-neutral “whole-energy system”;, and the shared development of the “Belt and Road”; energy corridor. The construction of an “energy powerhouse”; should follow a “three-phase”; strategic pathway: from 2025 to 2030, achieving peak primary energy consumption and “carbon peaking”;; from 2031 to 2050, energy production will achieve parity with consumption for the first time, striving for “energy independence”;; and from 2051 to 2060, aiming for “carbon neutrality”;, and establishing an “energy powerhouse”;. Building an “energy powerhouse”; will fundamentally safeguard national energy security, advance the achievement of carbon neutrality goals, provide Chinese solutions for global energy transition and green Earth construction, and support the modernization and great rejuvenation of the Chinese nation.